2016
DOI: 10.1016/j.humov.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Modification of impulse generation during piqué turns with increased rotational demands

Abstract: During initiation of a piqué turn, a dancer generates impulse to achieve the desired lateral translation and whole-body rotation. The goal of this study was to determine how individuals regulate impulse generation when initiating piqué turns with increased rotational demands. Skilled dancers (n=10) performed single (∼360°) and double (∼720°) piqué turns from a stationary position. Linear and angular impulse generated by the push and turn legs were quantified using ground reaction forces and compared across tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Rapid changes in direction, signaled by short duration turn phases, require the rapid generation of linear and angular impulses from ground reactions. These impulses accelerate the center of mass of the body in a new (desired) direction and also re-orient the body towards that direction [ 15 , 16 , 35 ]. Compared to lower performers, higher performers in our study exhibited shorter duration ground contacts and generated larger horizontal ground reactions that also had larger components tangent to (less normal to) the turn trajectories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid changes in direction, signaled by short duration turn phases, require the rapid generation of linear and angular impulses from ground reactions. These impulses accelerate the center of mass of the body in a new (desired) direction and also re-orient the body towards that direction [ 15 , 16 , 35 ]. Compared to lower performers, higher performers in our study exhibited shorter duration ground contacts and generated larger horizontal ground reactions that also had larger components tangent to (less normal to) the turn trajectories.…”
Section: Resultsmentioning
confidence: 99%
“…Turning agility can be defined as the ease with which a body changes direction [ 14 ]. Changing direction requires simultaneously satisfying linear and angular momentum requirements to redirect the body in the new (desired) direction [ 15 , 16 ]. Agility has been studied using a range of turning-while-running tasks with agility performance commonly defined by the time to complete the agility task [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…1a). 16,17,33 The purpose of this study was to examine strategies used by healthy young adults during each gait phase to accomplish the transverse-plane mechanical objectives of pre-planned and late-cued 90° turns. We hypothesized that in pre-planned and late-cued turns to the left, (1) during right single support phase, the greatest change in COM leftward linear velocity and average COM leftward linear acceleration are generated to redirect the COM trajectory towards the new direction of travel, and (2) during double support phases with the left foot in front of the body (left double support), the greatest change in transverse-plane angular momentum (Ht) and average transverse-plane moment are generated to rotate the body to the desired facing direction.…”
Section: Introductionmentioning
confidence: 99%
“…Prior turning research in athletic maneuvers has revealed that generating angular impulse by redirecting ground reaction forces during double support facilitates mitigating extraneous linear impulse and avoiding con icts between rotation and balance maintenance or COM translational goals. 16,17,33,34 For instance, during single support, if a large moment is applied from the ground reaction force, this force needs to be directed away from the COM, which may accelerate the COM in an undesired direction, or a direction away from the base of support (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Understanding the biomechanical interaction between dancers and floors could also provide insight for performance training in dance. 6 One area that has not been studied is how footwear may affect the twisting loads applied to the lower extremities during rotational movements.…”
mentioning
confidence: 99%